Bibliometric Analysis of the Utilization of Remote Sensing in Post-Disaster Environmental Recovery - Sekar Dwianti, Fitri Anggraeni; Trismadi; Syachrul Arief; Asep Adang Supriyadi (International Journal of Education, Vocational and Social Science, 2026)
Remote sensing is a strategic technology in spatial data collection that plays an important role in supporting post-disaster mitigation through the provision of fast, accurate, and wide-ranging information without direct interaction with affected areas. As the frequency and impact of natural disasters increase, a comprehensive study is needed to understand the development of research related to the use of remote sensing in environmental damage assessment and post-disaster recovery processes. This study uses bibliometric mapping methods to analyze international scientific publications that discuss the use of remote sensing in environmental damage assessment and post-disaster recovery over a period of 15 years. Data were obtained from reputable international journal databases Scopus and Google Scholar which were analyzed using VOSviewer software to identify patterns of author collaboration, major journals, and keyword co-occurrence. This analysis aims to map the knowledge structure, research trends, and dominant topics in the field. The results of the study show a significant increase in publications related to remote sensing, with a dominant focus on the use of satellite imagery for disaster impact identification, mapping environmental damage, and monitoring long-term environmental changes.